(untitled) (Research, Society and Development, 2021)
Human actions have caused changes in land use and coverage, which are often difficult to estimate. These changes can be recognized and mitigated through spatiotemporal data that make it possible to perceive changes in the landscape, as a subsidy, for the control of land use and coverage. This work presents a detailed time-space analysis of the dynamics of land use and coverage, in the Itacaiúnas River sub-basin, located in the Amazon region, Southeast Paraense, between the years 2004, 2010, 2012 and 2014. Topodata digital data and classification of the “terraclass” project from Lansat-5 and 8 satellites were used, as well as remote sensing tools to calculate and map the land use and land cover classes within the sub-basin unit. The results showed that during the studied period, the classes of land use and cover went through a great variation, with the progressive replacement of forests by areas with pasture, mining, and urban areas. Along with the rapid growth of these classes, the landscape of native vegetation has been replaced by an anthropized landscape, of a heterogeneous and fragmented character, as shown by the variations in the percentage of land use and cover classes.